RUANG PENYEMBUHAN UNTUK EFEK FISIK DARI KECANDUAN INTERNET - Clarin Sukri; J.M. Joko Priyono Santoso (Jurusan Arsitektur dan Perencanaan, 2019)
The existence of the internet today changes individual behavior in many aspects that not only have a positive impact but also have a negative impact on its users. The rise of internet abuse that occurs causes syndromes such as internet addiction and diseases that attack the individual's physique. Therefore a container for dealing with the physical effects of internet addiction in millennial adolescents becomes necessary. Container which also provides psychological support to individuals. The site is in the area with the most millennial growth and also with consideration of function utilization, the chosen site is Semanan, Kalideres, West Jakarta. The design method used is descriptive qualitative and experimental methods in designing where experiments are conducted by incorporating aspects of suitable architectural design in the project and synthesis analysis to find out the best architectural design strategies that can optimize the program of healing room facilities for victims of internet addiction. Thus the design recommendations chosen were the application of healing gardens and architectural healing to the design of